Oxford handbook of clinical dentistry - Rushworth, Bethany; Kanatas, Anastasios (Oxford University Press, 2020)
This essential pocket guide covers clinical dentistry in a concise format. All the fundamentals of clinical practice are included in a readily-accessible style. Now completely revised with a wealth of new information and full colour throughout
Keywords: Zahnmedizin; Electronic books